Exploring the Construction of a Long-Term Mechanism for the Co-Establishment of Animation Talent Cultivation Bases by Schools and Enterprises - Zhang, Xiru; Wang, Yu; Shi, Guang (Transactions on Economics, Business and Management Research, 2024)
The cooperation between schools and enterprises is a necessary path for the development goal of cultivating application-oriented talents. The core of this research is how to effectively establish a cooperation base for school-enterprise, joint talent cultivation, industry-education integration, and to establish an efficient base construction operation mechanism. This article takes the animation major of the School of Digital Media at Liaoning Communication University as a practical teaching base to introduce the methods and strategies for the construction of school-enterprise cooperation talent cultivation bases, focusing on the long-term mechanism for the construction and operation of school-enterprise cooperative talent cultivation bases.